2019
DOI: 10.1039/c9cc06586e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication-promoted synthesis of luminescent sulfur nano-dots for cellular imaging applications

Abstract: An ultrasonication-promoted strategy was proposed to synthesize luminescent sulfur nanodots, reducing the synthesis time from 5 days to several hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 30 publications
11
113
1
Order By: Relevance
“…Recently reported methods for SQDs preparation are seriously limited by the product yield. 5,6,8,12 In comparison, the yield of SQDs prepared under an O 2 atmosphere with a reaction time of 10 h could reach as high as 5.08%, which is more than vefold that of the SQDs prepared under an air atmosphere with a reaction time of even 60 h (0.87%). This indicates that reaction under an O 2 atmosphere could greatly increase the product yield value of SQDs (Fig.…”
Section: àmentioning
confidence: 90%
“…Recently reported methods for SQDs preparation are seriously limited by the product yield. 5,6,8,12 In comparison, the yield of SQDs prepared under an O 2 atmosphere with a reaction time of 10 h could reach as high as 5.08%, which is more than vefold that of the SQDs prepared under an air atmosphere with a reaction time of even 60 h (0.87%). This indicates that reaction under an O 2 atmosphere could greatly increase the product yield value of SQDs (Fig.…”
Section: àmentioning
confidence: 90%
“…In addition, Zhang et al reported the preparation of luminescent SQDs by ultrasonic treatment of sublimated sulfur, Na 2 S and PEG stabilizer in water. [27] After ultrasonication for 3 h, the SQDs with weak green fluorescence were formed. With extending the ultrasonication time, the fluorescent intensity of SQDs gradually enhanced, and meanwhile the emission wavelength gradually blue-shifted.…”
Section: Ultrasonication and Microwave Preparationmentioning
confidence: 99%
“…[21] In the past two years, impressive progress has been made in the synthesis of luminescent SQDs from elemental sulfur, including increasing PLQY (from 3.8 % to about 50 %), shortening reaction time (from 125 h to 4 h) and increasing reaction yield (from 0.87 % to 5.08 %). [23][24][25][26][27][28][29][30][31][32] However, considering the practical applications of SQDs, there are still some important issues that need to be addressed. Firstly, the PLQY of SQDs is still much lower than commercially available QDs, such as CdTe QDs and CdSe QDs (generally higher than 50 % and even exceeding 90 %).…”
Section: Ultrasonication and Microwave Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the peak at the binding energy of 170 eV indicates the sulfite oxidation into SO 3 − on the surface . The presence of elemental sulfur is proved by the appearance of peaks between 162 and 164 eV . Peaks corresponding to −OH and S=O groups located at 531.5 and 535.9 eV, and strong Na + signal, located at 1072.0 eV, are observed in the O 1s and Na 1s XPS spectra of the red‐emissive sulfur (Supporting Information, Figure S3), which further confirms that its main component is Na 2 SO 3 .…”
Section: Figurementioning
confidence: 99%